PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP INTENSI TURNOVER KARYAWAN DI ZEST HOTEL LEGIAN - Victoria Ananda Putri Pertiwi (Majalah Ilmiah Widyacakra, 2019)
This thesis was made with the title "The Influence of Leadership Style and Job Satisfaction on TurnOver Employees at Zest Hotel Legian" compiled by Victoria Ananda Putri Pertiwi (201520102498). To analyze the data that the author gets from the company, then the next author calculates using statistical calculations assisted with SPSS program with the following results: Partially leadership style (X1) has a positive and significant effect on intention to turn over (Y) on Zest Legian Hotel. This is evidenced from the regression coefficient b1X1 which has a positive value of 0.586, this is confirmed by the results of the calculation of t-count of 6.247 greater than t-table 1.676 with sig 0.000 smaller than dari = 5%. with beta coefficient of 0.627. Partially job satisfaction (X2) has a positive and significant effect on intention to turn over (Y) at Zest Hotel Legian. The significant influence is indicated by the calculation of t-count of 3.410 large from t-table 1.676 with sig 0.001 smaller than a = 5%. The results of the calculation simultaneously (together) leadership style (X1) and job satisfaction (X2) have positive and significant effect on intention to turn over (Y) at the Zest Hotel Legian. It is proven if the leadership style (X1) and job satisfaction are increased by one point causing turnover to increase by 0.995 (0.586 + 0.409). The amount of influence contributed by leadership style (X1) and job satisfaction (X2) on the intention of turn over (Y) at Zest Legian Hotel was 52.8% while the remaining 47.2% was influenced by other variables not discussed in this study. From the results of this study it can be concluded that Leadership Style and work peel are the basic things in organizing, where by giving attention / motivation to subordinates so that the desire for the intention to turn over at the Hotel Zest Legian can be reduced.